Analysis of Golden Period Delay in Severe Head Trauma Patients at Primary Health Care Facilities - Hardianti, Siti (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2023)
Severe head trauma is a major cause of global morbidity and mortality, especially in productive age. Rapid treatment in the golden period (first 1-2 hours post-trauma) is crucial to prevent serious complications. This study aims to analyze the factors that influence the delay in handling the golden period in severe head trauma patients in primary health facilities in Deli Serdang Regency. The design of this study was descriptive analytic with a cross-sectional approach. A sample of 110 severe head trauma patients was selected by purposive sampling according to the inclusion criteria. Data were collected through structured interviews and medical record analysis, then analyzed using the chi-square test to identify the relationship between independent and dependent variables. The results of univariate analysis showed that 70% of patients experienced delayed treatment beyond the golden period. The distribution of patient characteristics was as follows: 60% had low education, 55% had comorbid diseases, 52% were over 40 years old, and 58% were male. Bivariate analysis indicated a significant association between low education level (p=0.002; OR=5.966; 95% CI=2.02-17.56) and the presence of comorbid diseases (p=0.015) with delayed treatment. Patients with low education had a 5.966 times greater risk of delayed treatment compared to those with higher education. However, no significant association was found between age or gender and delayed treatment. These findings emphasize the importance of public education regarding the urgency of immediate treatment in severe head trauma, especially for individuals with low education. In addition, capacity building of primary healthcare facilities through training of medical personnel and provision of adequate equipment is needed to reduce delayed treatment and improve patient prognosis.